Head and Neck Schwannomas: A Tertiary Referral Single-Centre Experience - Öztürk, Murat; Şirin, Seher; Rahimli Alekberli, Fidan; Mutlu, Fatih; İşeri, Mete (ENT Updates, 2019)
Objective: The aim is to share our experience of the clinical features and important issues encountered in diagnosing and treating multiple head and neck schwannoma cases seen at our centre, all of which went on to have surgical treatment. Methods: This was a retrospective review of the medical records of cases over an 11-year period (2007–2018) diagnosed with schwannoma by post-surgical histopathology. The demographic characteristics of these cases, along with their clinical characteristics, namely, tumour location, preoperative diagnostic tests undertaken, surgical approach used, and any postoperative complications, including the management of such complications, were reviewed. Results: A total of 31 patients (18 male, and 13 female) were included in the study. Contrast-enhanced magnetic resonance imaging was the most commonly used pre-operative diagnostic method (77%). 58% of the cases were extra- and 42% intra-cranial. Extracranial schwannomas were noted to arise from several different areas of the head and neck region. The most common neurological deficit post-operatively was facial paralysis. Conclusion: Since head and neck schwannomas can develop from any area where the nerve sheath is present, they may present with a wide variety of non-specific symptoms. The treatment plan should be made with the anticipated preoperative and postoperative neurological deficit firmly in mind.